Neural-induced human adipose tissue-derived stem cell secretome exerts neuroprotection against rotenone-induced Parkinson’s disease in rats - Mahesh Ramalingam; Sujeong Jang; Jinsu Hwang; Hyong-Ho Cho; Byeong C. Kim; Han-Seong Jeong (Stem Cell Research & Therapy)
Abstract Background Parkinson’s disease (PD) is a multifactorial disease that involves genetic and environmental factors, which play an essential role in the pathogenesis of PD. Mesenchymal stem cells release a set of bioactive molecules called “secretome” that regulates intercellular communication and cargo transfer in signaling pathways for PD treatment. Thus, this study aimed to evaluate the neuroprotective effects of neural-induced human adipose tissue-derived stem cell (NI-hADSC)-conditioned medium (NI-hADSC-CM) and its exosomes (NI-hADSC-Exo) in a rotenone (ROT)-induced model of PD in rats. Methods The NI-hADSC-CM was collected from NI-hADSC after 14 days of neural differentiation, and its NI-hADSC-Exo were isolated using a tangential flow filtration system. ROT (1 mg/kg) was subcutaneously administered for 28 days to establish a model of PD in rats. The treatment of NI-hADSC-CM or NI-hADSC-Exo was intravenously injected on days 15, 18, 21, 24, and 27. Animal behavioral effects were explored via a rotarod test. After 28 days, histological and western blot analyses were performed to investigate the tyrosine hydroxylase (TH), α-synuclein (α-syn) aggregation, and downstream signaling pathways for experimental validation. Results NI-hADSC-Exo improved the motor balance and coordination skills against ROT toxicity. ROT reproduced the pathological features of PD, such as a decrease in TH-positive dopaminergic neurons and an increase in α-syn aggregation and glial fibrillary acidic protein (GFAP)-positive cells. NI-hADSC-CM and NI-hADSC-Exo improved the TH expression, decreased the Triton X-100 soluble and insoluble oligomeric p-S129 α-syn, and influenced the differential reactivity to astrocytes and microglia. Secretome treatment could reverse the ROT-induced damages in the neuronal structural and functional proteins, mitochondrial apoptosis, and caspase cascade. The treatment of NI-hADSC-CM and NI-hADSC-Exo ameliorated the ROT toxicity-induced serine-threonine protein kinase dysregulation and autophagy impairment to clear the aggregated α-syn. Conclusions NI-hADSC-CM and NI-hADSC-Exo significantly exerted neuroprotection by decreasing α-syn toxicity, inhibiting neuroinflammation and apoptosis, restoring autophagic flux properties, and promoting the neuronal function in ROT-injected rats; however, the influence of these treatments on signaling pathways differed slightly between the midbrain and striatum regions. Targeting α-syn degradation pathways provides a novel strategy to elucidate the beneficial effects of MSC secretome and future safe cell-free treatments for PD.